Risk Factors for Infection with Different Hepatitis C Virus Genotypes in Southern Brazil - Marisa Lúcia Romani Paraboni; Marina Dallagasperina Sbeghen; Fernando Herz Wolff; Leila Beltrami Moreira (The Scientific World Journal)
Objectives. To investigate the proportion of different genotypes in countryside microregions in southern Brazil, and their association with risk factors. Methods. Cross-sectional study including a convenience sample of patients who tested positive for HCV-RNA and were referred to a regional health center for genotyping, from December 2003 to January 2008. Data were obtained through the National Disease Surveillance Data System, from laboratory registers and from patient charts. Identification of genotypes was carried out using the Restriction Fragment Length Polymorphism “in house” technique. Independent associations with genotypes were evaluated in multinomial logistic regression and prevalence rates of genotypes were estimated with modified Poisson regression. Results. The sample consisted of 441 individuals, 41.1±12.0 years old, 56.5% men. Genotype 1 was observed in 41.5% (95% CI 37.9–48.1) of patients, genotype 2 in 19.3% (95% CI 15.0–23.6), and genotype 3 in 39.2% (95% CI 35.6–43.0). HCV genotype was significantly associated with gender and age. Dental procedures were associated with higher proportion of genotype 2 independently of age, education, and patient treatment center. Conclusions. The hepatitis C virus genotype 1 was the most frequent. Genotype 2 was associated with female gender, age, and dental procedure exposition.